Rescue of Murine Sarcoma Virus from a Sarcoma-Positive Leukemia-Negative Cell Line: Requirement for Replicating Leukemia Virus - Peebles, P. T. (1971)
The nature of murine sarcoma virus (MSV) “defectiveness” was investigated by employing an MSV-transformed mouse 3T3 cell line which releases noninfectious virus-like particles. Rescue kinetics of MSV, observed after murine leukemia virus (MuLV) superinfection of these “sarcoma-positive leukemia-negative (S + L −)” mouse 3T3 cells, consisted of a 9− to 12-hr eclipse period followed by simultaneous release of both MSV and MuLV with no evidence for release of infectious MSV prior to the production of progeny MuLV. Addition of thymidine to the growth medium of MuLV-superinfected S + L − cells at a concentration suppressing deoxyribonucleic acid synthesis inhibited the replication of MuLV and the rescue of MSV. MSV production closely paralleled MuLV replication under a variety of experimental conditions. These results suggest that replication of MuLV is required for the rescue of infectious MSV from S + L − cells and that one (or more) factor, produced late in the MuLV replicative cycle, is utilized by both viruses during virion assembly. During the course of these experiments, virus stocks were recovered which contained infectious MSV in apparent excess over MuLV. These stocks were used for generating new S + L − cell lines by simple end point dilution procedures.